PENGARUH RASIO BAHAN BAKU TEPUNG KOMPOSIT (UBI KAYU, JAGUNG DAN KEDELAI HITAM) PADA KUALITAS PEMBUATAN BERAS ANALOG - Isti Pudjihastuti; Edy Supriyo; Hafiz Rama Devara (Vocational School Diponegoro University, 2021)
The increase population affects an increase in total of consumption of Indonesian people towards rice, which encourages Indonesia to import rice. One of the alternatives that can be done is by using potential non-rice raw materials such as tubers. In this study, the raw materials for composite flour from cassava (Manihot esculenta), corn (Zea mays) and black soybeans (Glycine Sojo) were used, which are the basic ingredient for analog rice. The purpose of this study was to examine the effect of raw material composition on nutritional value (carbohydrate, protein, fat, water and ash content) analog rice compared to ordinary rice, examine the physico-chemistry (kamba density, water absorption and cooking time) of analog rice compare to paddy rice and also to define raw material composition and best temperature, organoleptic test covering color, aroma, texture and taste. The process of making analog rice consists of several stages of research, such as the stage of making composite flour, cooking the composite flour dough, making analog rice, drying analog rice and analyzing the results. The variables used were the ratio of flour composition and the effect of extrusion temperature. Based on proximate analysis on various compositions, obtained sample 5 (60% cassava flour, 15% corn flour and 25% black soybean flour) as analog rice with the best formulation. Based on the proximate analysis of the effect of temperature, the temperature was 75 °C as the optimum temperature for the extraction process. The results of the physical analysis of the best analog rice in this study showed that analog rice from a composite of cassava flour, corn flour and black soybean flour had a kamba density of 0.46 g / mL, a water absorption capacity of 60.52% and a cooking time of 46 minutes. In this sample, analog rice has a texture, aroma and appearance similar to rice in general, although analog rice from composite flour tends to have a savory taste arising from black soybeans.